factorization of the polynomial (x-y)² a²+2(x-y)(x+y) ab+b2(x+y)²
Answers
Answered by
1
Step-by-step explanation:
Here's your answer!!
There are 2 solutions possible...
1) Substitute a(x-y) = m AND b(x+y) = n
Now given equation re-writes as m² + 2mn + n².
The re-written equation factotises as (m+n)², or we can say there is only one factor (m+n).
Now, substitute back the values of m and n.
The single factor of the given equation is
➡ {a(x-y) + b(x+y)}.
2) This is if the form A² + 2AB + B² = (A+B)²
Where A = a(x-y) , B = b(x+y)
Hence the factors are..
[ a(x-y) + b(x+y) ]² or
[ a(x-y) + b(x+y) ][ a(x-y) + b(x+y) ]
Similar questions